2018
DOI: 10.5114/ms.2018.74820
|View full text |Cite
|
Sign up to set email alerts
|

Conflict and facilitation between family and occupational roles versus work-related stress in the teachers’ group

Abstract: Introduction: Like all public service workers, teachers face extremely challenging demands. Numerous studies indicate that teachers of any profession encounter some of the highest levels of work-related stress. Aim of the research: The aim of this study is to examine the impact of conflict and facilitation between occupational and family roles on the levels of work-related stress experienced by teachers. Material and methods:The study included 120 teachers (60 women and 60 men), all of whom were married. Occup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Higher stress levels were experienced by women than by men. Similar results were obtained by other researchers [5,17,21,22].…”
Section: Discussionsupporting
confidence: 92%
“…Higher stress levels were experienced by women than by men. Similar results were obtained by other researchers [5,17,21,22].…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have demonstrated a positive relationship between teachers' well-being and their efficacy in teaching [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. However, practical and applied research on training programs to improve teacher well-being and efficacy is still needed, particularly in light of the extreme challenges posed by the COVID-19 crisis.…”
Section: Work-related Stress Among Teachersmentioning
confidence: 99%
“…The ENRICH Marital Satisfaction (EMS) Scale (Fowers & Olson, 1993) was adapted into Polish (Lachowska, 2012). The 10-item EMS is a subscale of the ENRICH Marital Inventory.…”
Section: Methodsmentioning
confidence: 99%
“…The Parental Distress Scale (Pearlin, 1975) as adapted into Polish (Lachowska, 2012) was used to measure stress related to parenthood. The measure is based on respondents' self-reports of their feelings of distress in their lives as parents.…”
Section: Methodsmentioning
confidence: 99%